Oral presentation On the ecotoxicity of pharmaceuticals and their photo-transformation mixtures - Vasquez Christodoulou, Marlen (My University, 2026)
Tarapoulouzi M, Vasquez MI, Lambropoulou D, Fatta-Kassinos D On the ecotoxicity of pharmaceuticals and their photo-transformation mixtures, oral presentation, XENOWAC II Challenges and solutions related to xenobiotics and antimicrobial resistance in the framework of urban wastewater reuse, Limassol, Cyprus, 10-12 October 2018.